Response of rootstocks to stem canker and the production and quality of melon under protected cultivation - Ito, L. A. [UNESP]; Braz, L. T. [UNESP]; Castoldi, R. [UNESP]; Charlo, H. C O [UNESP] (My University, 2008)
Two tests were performed. In the first, resistance to Didymella bryoniae was determined for the following genotypes: the pumpkins 'Ikky', 'Agroceres', 'Kirameki' and 'Shelper', watermelon progenies 1a, 2a, 3a, 5a, 1b, 2b, 3b and 5b, and 'Gherkin' (C. anguria). The plants were inoculated with the fungus during transplanting. The evaluations of the test were performed every 15 d according to a scoring scale adopted by Dusi et al. (1994). The second test examined compatibility among the rootstocks x grafts, and their effects on production. The rootstocks, 5 pumpkins including 'Ikky', 'Agroceres', 'Kirameki', 'Shelper', six watermelon progenies 1a, 2a, 5a, 1b, 2b and 5b, and one 'Gherkin', were planted one week before planting of the grafted 'Bônus No. 2' melon. The experiments were carried out with 12 treatments, including the control ('Bônus No. 2') with 3 replications with 14 grafted plants per each replication. For the first test, the first three evaluations (at 15, 30 and 45 d after inoculation) did not show characteristic lesions of stem canker, but progeny 3b was found to be susceptible in evaluations performed at 60 and 75 d after inoculation. Progeny 3a demonstrated intermediate susceptibility, while progenies 1a, 2a, 5a, 1b, 2b and 5b, the pumpkins 'Kirameki', 'Shelper', 'Ikky' and 'Agroceres', and 'Gherkin', showed resistance to Didymella bryoniae. In the second test, watermelon progenies 1a, 5a, 1b and 2b, and the pumpkins 'Kirameki', 'Shelper', 'Ikky' and 'Agroceres' showed a level of grafting success of 100%, while results with progenies 2a and 5b, and 'Gherkin' were different in grafting success, respectively 91.67, 98.33 and 43.33%. For other fruit parameters, weight, longitudinal and transverse diameters, pulp thickness and level of total soluble solids, there were no differences among the treatments.
Keywords: Cucumis melo; Didymella bryoniae; Production; Rootstock; Citrullus lanatus var. lanatus; Cucumis; Cucumis anguria; Cucurbita; Fungi